Evaluation of prognostic risk factors of triple-negative breast cancer with 18F-FDG PET/CT parameters, clinical pathological features and biochemical indicators - Zhu, Lei; Yang, Xin; Zhang, Jiying; Wang, Shuling; Wang, Yulong; Wan, Xing; Zhu, Xiang; Song, Xiuyu; Tong, Zhongsheng; Yang, Meng; Zhao, Weipeng (Frontiers in Cell and Developmental Biology, 2024)
Abstract Objective: Breast cancer is a heterogeneous disease comprising various molecular subtypes, including luminal A, luminal B, human epidermal growth factor receptor-2 (HER2) positive, and triple negative types, each with distinct biological characteristics and behaviors. Triple negative breast cancer (TNBC) remains a particularly challenging subtype worldwide. This study aims to evaluate whether Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (18F-FDG PET/CT) parameters, clinical pathological features, and biochemical indicators serve as prognostic risk factors for TNBC. Additionally, we explore correlations between biochemical indicators and 18F-FDG PET/CT parameters. Materials and methods: We conducted a retrospective analysis of 95 TNBC patients who underwent preoperative 18F-FDG PET/CT examinations at Tianjin Medical University Cancer Institute & Hospital from 2013 to 2018. Collected data included 18F-FDG PET/CT parameters, clinical and pathological features, and biochemical indicators. We used Kaplan-Meier survival analysis and multivariate Cox regression analysis to evaluate associations between 18F-FDG PET/CT parameters /biochemical indicators and disease free survival (DFS)/overall survival (OS). The log-rank test determined significant differences in survival curves, and the Spearman correlation coefficient analyzed correlations between quantitative variables. Visualization and analysis were performed using R packages. Results: Among 95 TNBC patients, mean standardized uptake value (SUVmean) was significantly correlated with DFS. Fasting blood glucose (FBG), α- L-fucosylase (AFU) and Creatine kinase (CK) were independent predictors of DFS, while Precursor albumin(PALB) and CK were independent predictors of OS. FBG showed correlations with SUVpeak and SUVmean, and CK was correlated with peak standardized uptake value (SUVpeak). Our results indicated that 18F-FDG PET/CT parameters and biochemical indicators may constitute a new prognostic model for TNBC patients post-surgery. Conclusion: SUVmean, FBG, AFU and CK are predictive factors for DFS in TNBC patients post-surgery, while PALB and CK are predictive factors for OS, which prompts us to pay more attention to these indicators in clinical practice. And 18F-FDG PET/CT parameters and biochemical indicators have potential utility in constituting a new prognostic model for TNBC patients post-surgery.